The Impact of Short-Form Content TikTok on English Language Learning Development among Generation Z: A Case Study of Students at Institut Elkatarie" - Alfitri, Bahya (MODELING: Jurnal Program Studi PGMI, 2024)
This study investigates the impact of TikTok’s short-form content on the development of English language skills among students at Institut Elkatarie. Employing a quantitative approach with a quasi-experimental design, the research compares two groups of students: an experimental group using TikTok as a supplementary learning tool and a control group following traditional classroom methods. The findings reveal that the experimental group showed significant improvement in listening comprehension, pronunciation, and vocabulary acquisition, with a 22.9% increase in their post-test scores compared to only an 8.2% improvement in the control group. Data were collected through pre- and post-tests, a TikTok usage questionnaire, and in-depth interviews. The study confirms that TikTok’s engaging, authentic content motivated students, aligning with constructivist learning theory and intrinsic motivation theory, which emphasize contextual and enjoyable learning experiences. The results suggest that TikTok can be a valuable tool in enhancing language learning, particularly in areas where traditional methods may fall short, such as informal language use and listening skills. This research contributes to the growing body of knowledge on digital platforms in education, offering insights into how social media can be effectively integrated into language learning practices.